Sensory Quality Characteristics of Skipjack Tuna Crackers (Katsuwonus pelamis) Substituted with Tuna Bone Flour - Rasna Wahab; Ahmad Talib; Ruslan A. Daeng (BIOSAINSTEK, 2026)
Indonesia is an archipelagic country with vast marine resources, dominated by pelagic fish such as tuna and skipjack tuna. Skipjack tuna (57,126.3 tons/year in North Maluku) is often processed traditionally, but parts other than the meat, such as bones, are generally discarded. Fish bones are a waste product rich in calcium and phosphorus, which are important for the body. Utilizing this waste into bone meal can increase the nutritional value of processed fishery products, such as fish crackers. The research was conducted at the UMMU Fishery Product Technology Laboratory in January 2024. The methods included making tuna bone meal (boiled, dried, and ground) and making skipjack fish crackers. The crackers were made in four formulations: A0 (control, 0% bone meal), A1 (10%), A2 (20%), and A3 (30%). The main analysis was a sensory quality test (organoleptic) for appearance, aroma, taste, and texture, followed by a Least Significant Difference (LSD) test if there was a significant effect. The organoleptic test results showed that the addition of tuna fish bone meal had a significant effect on all sensory quality parameters (appearance, aroma, taste, and texture). The highest values for all parameters (except appearance, which was highest in A4/30%) were generally achieved at a 30% fish bone meal addition concentration (A3 or A4 depending on the naming in the table), indicating an increase in panelist acceptance as the bone meal substitution increased. This demonstrates the potential for utilizing fish bone waste.